Low-cycle fatigue behavior and deformation mechanisms of a dual-phase Al0.5CoCrFeMnNi high-entropy alloy. (October 2022) - Lu, Kaiju; Knöpfle, Fabian; Chauhan, Ankur; Jeong, H.T.; Litvinov, Dimitri; Walter, Mario; Kim, W.J.; Aktaa, Jarir
Graphical abstract: Highlights: Al0.5 CoCrFeMnNi demonstrates higher cyclic stress resistance than CoCrFeMnNi, meanwhile maintaining comparable cyclic strain resistance at low-to-medium strain amplitudes. Deformation in Al0.5 CoCrFeMnNi is accommodated by dislocation slip, whose mode changes from planar slip to wavy slip with increasing strain amplitude. Upon comparison with Al0.5 CoCrFeNi and CoCrNi, this work sheds light on strategies to optimize fatigue resistance of HEAs. Abstract: We uncover the low-cycle fatigue response and deformation mechanisms of a dual-phase Al0.5 CoCrFeMnNi high-entropy alloy (HEA) by comparing to CoCrFeMnNi HEA. Al0.5 CoCrFeMnNi demonstrates higher cyclic stress resistance, meanwhile maintaining comparable cyclic strain resistance at low-to-medium strain amplitudes. Microstructural investigations revealed dislocation slip as the primary deformation mechanism, which changes from planar slip to wavy slip with increasing strain amplitude. The enhanced cyclic stress resistance is related to precipitation hardening and improved solid solution strengthening. Meanwhile, the comparable cyclic strain resistance is ascribed to their similar deformation mode. Lastly, comparisons with Al0.5 CoCrFeNi and CoCrNi alloys provide strategies for tailoring HEAs with enhanced fatigue resistance.